"Nobody's Failing at Going Through a Global Pandemic": Lessons and Tensions in Social Work Education. (18th August 2021) - Paceley, Megan S.; Cole, Sarah J.; Robinson, Jennifer A.; Carr, Kortney A.; Jen, Sarah; Riquino, Michael R.; Mitra, Samantha; Wright, Kelechi C.
ABSTRACT: Social work educators prepare students to respond to crises across system levels. A global pandemic or large-scale disasters, however, present challenges educators are ill prepared for. This study explored the experiences of BSW and MSW students during the COVID-19 pandemic. With a trauma-informed pedagogy framework, a team of faculty and students conducted in-depth interviews with social work students at a Midwestern school of social work. Thematic analyses revealed two categories. First, broad lessons learned included clear guidelines for educators across higher education. Second, three themes revealed tensions in student reactions to their experiences during COVID-19: (a) loss versus safety, (b) flexibility versus structure, and (c) affective responses versus competing responsibilities. Findings are discussed and implications for social work are identified.